2009
DOI: 10.2528/pierc08112002
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Detection of Landmines From Acoustic Images

Abstract: Abstract-The Laser Doppler Vibrometer (LDV)-based Acoustic toSeismic (A/S) landmine detection system is one of the reliable and powerful landmine detection systems. The interpretation of the LDVbased A/S data is performed off-line, manually, depending heavily on the skills, experience, alertness and consistency of a trained operator. This takes a long time. The manually obtained results suffer from errors, particularly when dealing with large volumes of data. This paper proposes some techniques for the automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Without preprocessing, the detection probability of landmines is about 90%. Morphological preprocessing can increase this detection probability to about 97% with a small false alarm probability but all these probabilities are in the absence of any type of noise [1,2]. The issue of noise effect is an issue which is rarely studied by researchers in this area.…”
Section: Traditional Landmine Detection Approachesmentioning
confidence: 96%
See 2 more Smart Citations
“…Without preprocessing, the detection probability of landmines is about 90%. Morphological preprocessing can increase this detection probability to about 97% with a small false alarm probability but all these probabilities are in the absence of any type of noise [1,2]. The issue of noise effect is an issue which is rarely studied by researchers in this area.…”
Section: Traditional Landmine Detection Approachesmentioning
confidence: 96%
“…These techniques begin by intensity thresholding of images to reject the dark background and then the detection of landmines based on their dimensions [1,2]. The drawbacks of these techniques lie in their inability to detect landmines with small dimensions in the images and their inability to reject background noise in the intensity thresholding approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Federal Bureau of Investigations, it suffices to identify a fingerprint by matching 12 minutiae, but it has been reported that in most cases, 8 matched minutiae are enough. [15,16]. Many obstacles are faced in removing these buried landmines, such as the loss or absence of maps or information about these mines or even the areas, where they were laid in, the change of mine locations due to climatic and physical factors, the large variety of types of AP and AT landmines, and the high costs needed to remove mines.…”
Section: Pattern Characteristics and Recognitionmentioning
confidence: 99%
“…These techniques begin by intensity thresholding of images to reject the dark background and then detection of landmines based on their dimensions [15,16]. The drawbacks of these techniques lie in their inability to detect landmines with small dimensions and their inability to reject background noise in the intensity thresholding approach.…”
Section: Pattern Characteristics and Recognitionmentioning
confidence: 99%